Public Listed Companies Takeovers Comparison Under Indonesian and Malaysian Law - Maria Ulfah Tidar; Kurnia Toha (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The current condition of business competion is getting tighter. This causes the company to compete to maintain its existence. One way to do that is by restructuring the company. Takeover is one type of corporate restructuring. Takeover is a legal action carried out by a legal entity or individual to take over company shares resulting in a transfer of control over the company. The purpose of this legal research is to increase knowledge in the field of public listed companies takeovers based on Indonesian and Malaysian Law which can be benefit to legal practitioners. This research is a normative legal research using statutory and comparative approach. The data used in this research is secondary data. The results of the study are a public listed company that undertakes a takeover in not only subject to the laws and regulations regarding limited liability companies, but also must comply with the provisions of the capital market laws and regulation. After the takeover process occurs, the expropriating party must carry out a mandatory tender offer process. There are differences in terms of public listed companies takeover process between Indonesian and Malaysian Law including the requirements to become a new controller, minority shareholder rights, and takeover’s impact regulation on business competition.